Study of Dual Brand in Indonesia Tourism Communication - Teguh, Monika; Bungin, Burhan; Wono, Hilda Yunita; Santoso, Theodore Jason (Jurnal Komunikasi, 2022)
One of the main parts of a country's tourism communication is the tourism destination brand. The Indonesian tourism destination brand itself has changed several times since 2008. At that time, the brand used was Visit Indonesia 2008, then the following year it changed to Visit Indonesia 2009. Then in 2010 until 2021, Indonesia uses two brands at once, namely Wonderful Indonesia and Pesona Indonesia, even though the Indonesian tourism destination in question is one, namely Indonesia's destination. In fact, the use of these two brands has not been able to show a positive performance in bringing in tourists or making Indonesian tourism destinations famous and remembered by potential tourists. Therefore, we need a study on the existence of this dual brand, which is the purpose of this scientific article The subject of this study is the Indonesian tourism brand, Wonderful Indonesia, while the object studied is the duality in the use of the brand. This study was made using qualitative methods, specifically by using literature review. The method of data collection is documentation. This study uses a narrative method in its discussion. From this study, it can be explained that the brand personality of the Indonesian tourism destination brand is still weak. This is mainly due to the dual brands Wonderful Indonesia and Pesona Indonesia which have two different meanings and have not been able to represent tourist destination areas in Indonesia. In the end, this makes brand awareness, brand equity and brand loyalty are not formed. Therefore, it would be better if only one tourism destination brand can be formulated. The brand should represent various tourist destination areas and can be used consistently for a long time.